Strategi Peningkatan Loyalitas Karyawan Pada Hotel X di Bumi Serpong Damai Tangerang Selatan - Ingkadijaya, Rahmat; Wulan, Saptarining; Rahmanita, Myrza; Sugeng, Novita Widyastuti; Cailendra Poetry, Indri Maheswari (Jurnal Ilmiah Pariwisata, 2026)
This study is motivated by the high employee turnover rate at Hotel X Bumi Serpong Damai, South Tangerang City, which indicates problems related to employee loyalty. Employee loyalty is an important factor in maintaining organizational stability and is influenced by workload, remuneration, and the work environment experienced by employees. These factors play a significant role in shaping employee satisfaction, engagement, and commitment to the organization. This study aims to analyze the perceptions of management and employees regarding workload, remuneration, and the work environment, identify perception gaps, and formulate strategies to improve employee loyalty. The study uses a descriptive quantitative approach with a survey method through questionnaires distributed to 54 respondents consisting of employees and management. Data analysis was conducted using validity, reliability, and normality tests, gap analysis, and Cartesian diagrams with the assistance of SPSS. The results indicate perception gaps, particularly in remuneration and working hours, where employees perceive compensation as not fully aligned with their workload. Although the work environment is considered conducive, stronger supervisor support and recognition are needed to enhance employee loyalty and long-term organizational commitment. Keywords: employee loyalty, workload, remuneration, work environment, employee turnover